Net Profit Margin (Npm) Analysis in Measuring SK Hynix Inc.'S Financial Performance Against Semiconductor Market Fluctuations 2020-2024 - Itto Turyandi; Wanda Alicia Andin; Muhammad Rangga Wibiksana; Silvi Andriyani Wardani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Semiconductors underpin the digital economy, yet the memory market is highly cyclical, exposing chipmakers to sharp margin compression during oversupply and price corrections. This study examines SK hynix’s “extreme recovery” using Net Profit Margin (NPM) as the focal performance metric and interprets the recovery through cost-management theory, cost–volume–profit logic, and Activity-Based Costing (ABC). Adopting a quantitative descriptive design with a single-case study approach, the analysis relies on publicly available SK hynix financial statements from 2020–2024. Key variables include NPM (net income/revenue), revenue, and operating expenses; descriptive statistics, trend and percentage-change analysis, and Excel-based visualizations are complemented by triangulation with industry news. Results reveal a pronounced V-shape: NPM declined from 22.36% (2021) to 5.02% (2022) and −27.88% (2023), then rebounded to 29.9% (2024). The turnaround aligns with a higher-value product mix (AI HBM) and cost control, offering implications for investors and industrial policy.